Complementary alternative medicine in rheumatic diseases: Causes, choices, and outcomes according to patients - Gozcu, Ersin; Cakmak, Ismail; Oz, Burak; Karatas, Ahmet; Akar, Zeynel Abidin; Koca, Suleyman Serdar (Aves, 2022)
Objective: The knowledge of physicians about complementary and alternative medicine (CAM) applications is limited. However, especially in chronic diseases, patients and their relatives can often refer to CAM applications. Rheumatic diseases are chronic in nature presenting with a wide clinical spectrum. Despite developing treatment options, achieving treatment goals may not always be possible. For this reason, patients seek different treatment and use traditional and complementary medicine. The aim of this study was to investigate causes, consequences, and the frequency of applying to CAM in rheumatic diseases. Methods: Ninety-five patients admitted to the rheumatology outpatient clinic were enrolled in the study. Health assessment questionnaire and short-form-36 were used to determine the quality of life of patients. Anxiety and depression symptoms were screened by the Hospital Anxiety and Depression scale, a questionnaire that was filled-in by the patients themselves. Also, patients were questioned about their place of residence, level of education, diagnosis, CAM modality types, application reasons, and outcomes. Chi-square test was used to analyze categorical data. Parametric data were analyzed using Student t-test, and nonparametric data were analyzed using Mann-Whitney U test. Results: Thirty-two of our patients had applied to CAM modalities (phytotherapy [34.45%], cupping therapy [21.8%], acupuncture [12.5%] hirudotherapy [12.5%], food supplement [12.5%] and ozone treatment [6.25%]). Only 31.3% of the patients informed their doctors about CAM applications. 47.8% of fibromyalgia patients and 29.2% of patients with inflammatory rheumatic diseases had applied to CAM. Gender. working status, income level, smoking, and alcohol habits were not associated with the application to CAM. However, none of the residents of the village, 14.3% of the residents of the district center, and 41.1% of the residents of the city center had applied to CAM modality. The rate of applying to CAM was 18.2% for those who cannot read and write. The application ratio of CAM is over 40% a mong secondary school, high school, and university graduates. Conclusion: Among patients with rheumatic diseases, application to CAM is quite common. Very few patients inform their physicians about applying to CAM. Contrary to what is presumed, the rate of applying CAM applications is lower among those living in rural areas and with low education levels.
Keywords: Complementary and alternative medicine; rheumatic diseases; fibromyalgia